Experience of the spouse of a woman with breast cancer undergoing chemotherapy: a qualitative case study - Rhyquelle Rhibna Neris; Márcia Maria Fontão Zago; Maria Ângela Ribeiro; Juliana Pena Porto; Anna Cláudia Yokoyama dos Anjos (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objective: To identify the meaning attributed to the experience of a spouse of a woman with breast cancer undergoing chemotherapy. Methods: Descriptive study, with a theoretical-methodological orientation based on medical anthropology and utilizing an ethnographic case study strategy. Data were collected through semi-structured interviews and participant observation. Results: The meanings revealed that the diagnosis cause suffering. Chemotherapy was seen as giving hope of healing the wife's cancer. During this process, the spouse had to deal with the strong adverse effects of the treatment and subordinate to his wife to reduce the conflict experienced by the couple, which violated the rules of his masculinity. Religion and family were important support networks on this path. Final considerations and implications for practice: The results showed the importance of considering cultural aspects of spouses when they are faced with disease in their wives. The way spouses deal with breast cancer will depend on their cultural systems. Nursing care must be comprehensive and extend to spouses whose wives have breast cancer.